Unsur-Unsur Sekuler Dalam Feminisme - dan Ahmad Syadzali, Zakiyah (Muadalah, 2015)
Feminism is a movement that is fighting for womenâs rights and for women as the mostÂ instrumental ones who enable humans to evolve and grow quantitatively. However,Â because in fact, their biological superiority are often neglected, they are sometimesÂ underestimated by the opposite sex who tend to manipulate them into merely humanÂ reproduction machines, or even used as to satisfy biological needs, and were subjected toÂ more injustice. This fact has inspired feminist to fight for the justice in order to restore theÂ rights of women in equality. In this case, the writers have used the theory of desecrationâÂ browsing the secular nuances in feminist theology. At first, the feminism struggle doesÂ have a noble purpose. Yet, their empathy for the fate of the oppressed women have madeÂ them to be overly sensitive and tends to be secular. They assume that religion has playedÂ a role in the occurrence of inequality, such as the Verses or hadith of Misoginik which hasÂ resulted in a gender bias and the emergence of hegemony that is detrimental to women